Influência do peso dos ovos de reprodutoras Leghorn sobre as características dos ovos incubáveis e dos pintos de um dia - Crosara, Flávia de Sousa Gomes (2013)
The weight´s effect on egg´s quality, performance characteristics and incubation of chicks were observed in two experiments. Three treatments were used, defined by the weight of the eggs, breeding Leghorn 38 weeks old: small (S) 53 to 57g, medium (M) 58 to 62g and large (L) 63 to 67g. We have evaluated: a) the eggs - strength and shell thickness, Haugh units (HU), albumen height and percentage of egg compounds b) in incubation - eggs weight loss , hatching and embryo diagnosis, c) in one day old chicks in the yolk sac: weight and length of the chick, absolute and relative weight of the yolk sac, d) dry material (DM), crude protein (CP) albumen´s energy , and the yolk sac. Eggs range of different weights produced by Leghorn breeders of the same age (38 weeks) did not show differences among them for shelll strength, relative weight of albumen and yolk, albumen and yolk in DM and gross energy in the yolk. There are differences in the shell thickness, UH, albumen height, absolute weight of egg components, the relative weight of shell, the yolk and albumen protein and gross energy albumen. In the incubation, the weight loss of eggs and the hatch decreases with increasing egg weight range. Unhatched eggs increase with the increase of initial mortality and pecked alive and dead. The chick weight, absolute and relative weight of the yolk sac are directly proportional to the weight of the egg. The proportion of protein in the yolk sac decreases with increasing egg weight and gross energy content is higher in the yolk sac of chicks hatched from medium eggs.